UPAYA MENINGKATKAN HASIL BELAJAR MATA PELAJARAN PENDIDIKAN PANCASILA MELALUI MEDIA FLASHCARD KELAS V SD - Fernanda Putri Wulan; Nurul Febrianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The success of learning in elementary schools does not only depend on the content being taught but also on how teachers present media that are engaging and relevant to students’ needs. With this in mind, the present study explored the effectiveness of using flashcards to improve student learning outcomes in Civic Education for fifth graders at SD Negeri Pejuang V. The research was carried out using Classroom Action Research (CAR) based on Kemmis & McTaggart’s model, which involves four stages: planning, implementation, observation, and reflection. The study involved 30 students from class V.3, with data collected through tests, observations, and interviews to provide a comprehensive view of students’ progress. The findings were encouraging: in the first cycle, the mastery level rose from only 20% in the pretest to 66.7% in the posttest. This improvement continued in the second cycle, where the mastery rate increased from 53.3% to 86.7%. Beyond academic achievement, both teacher and student engagement in the learning process also showed notable growth. In the second cycle, teacher activity reached 94.6%, while student activity was recorded at 87.5%. This means that flashcards not only help students to better understand the material and improve their learning outcomes, but also enliven the classroom atmosphere, foster more communicative interaction, and encourage students to participate more actively.